SISTEM INFORMASI AKUNTANSI PENGGAJIAN (STUDY KASUS PADA CV. SGM) - Takiyuddin, Takiyuddin (STMIK Kaputama, 2018)
The volume of expenditure for labor costs and related payroll has a significant effect on the net income of most business enterprise. Accordingly, it is important that the accounting information System of payroll provides safeguards to insure that payment are in accord with management’s general plans and its specific authorizations. All employment of a firm expect and are entitled to receive their remuneration at regular intervals following the close of each payroll period. Regardless of the number of employees and of intricacies in computing the amounts to be paid, the accounting information system of payroll must be designed to process the necessary data quickly and assure payment of the correct amount to each employee. It is essential that the system provide adequate safeguards againt payment to fictitious person and other misappropriations of fund.CV.SGM is engaged in passenger transportation and freight forwarding have done accounting information system of payroll simply.